Pengaruh Penambahan Kitosan dalam Pembuatan Biodegradable Foam Berbahan Baku Pati - Nanik Hendrawati; Yulia Irna Lestari; Putri Anggraini Wulansari (Jurnal Rekayasa Kimia & Lingkungan, 2017)
Biodegradable foam is an alternative packaging to replace the expanded polystyrene foam packaging currently in use.   Starch has been used to produce foam because of  its low cost, low density, low toxicity, and  biodegradability. Chitosan has been added to improve mechanical properties of product . The   effect of  variation on chitosan amount  and  starch types  was investigated in this study.  The amount of  chitosan  was varied as 0; 5; 10; 15; 20; 25; and  30 % w/w and starch types were used in this research were cassava, Corn and sago starch. Biodegradable  foam was produced by using baking process method, all of material (Starch, Chitosan solution,  Magnesium Stearate, Carrageenan, Glyserol, Protein Isolates  dan polyvinil alcohol (PVOH)  were mixed with kitchen aid mixer. The mixture was poured  into mold and heated in an oven at 125 oC for 1 hour. Then, foam was tested for its mechanical properties, water absorption  and biodegradability and  morphology (SEM).  The results show that  foam made from sago starch had lower water absortion than those made from cassava and corn starch.   While, foam made from cassava starch  was more biodegradable than the other foam.  Biodegradable foam based sago starch and 30 % w/w of Chitosan adition  gave the  best performence in tensile stress that  is 20 Mpa